Lead-free halide perovskite Cs2AgBiBr6/bismuthene composites for improved CH4 production in photocatalytic CO2 reduction - Sena,MS; Cui,J; Baghdadi,Y; Rattner,E; Daboczi,M; Lopes-Moriyama,AL; dos,Santos AG; Eslava,S (ACS Applied Energy Materials, 2023)
CO2 photocatalytic conversion into value-added fuels through solar energy is a promising way of storing renewable energy while simultaneously reducing the concentration of CO2 in the atmosphere. Lead-based halide perovskites have recently shown great potential in various applications such as solar cells, optoelectronics, and photocatalysis. Even though they show high performance, the high toxicity of Pb2+ along with poor stability under ambient conditions restrains the application of these materials in photocatalysis. In this respect, we developed an in situ assembly strategy to fabricate the lead-free double perovskite Cs2AgBiBr6 on a 2D bismuthene nanosheet prepared by a ligand-assisted reprecipitation method for a liquid-phase CO2 photocatalytic reduction reaction. The composite improved the production and selectivity of the eight-electron CH4 pathway compared with the two-electron CO pathway, storing more of the light energy harvested by the photocatalyst. The Cs2AgBiBr6/bismuthene composite shows a photocatalytic activity of 1.49(±0.16) μmol g–1 h–1 CH4, 0.67(±0.14) μmol g–1 h–1 CO, and 0.75(±0.20) μmol g–1 h–1 H2, with a CH4 selectivity of 81(±1)% on an electron basis with 1 sun. The improved performance is attributed to the enhanced charge separation and suppressed electron–hole recombination due to good interfacial contact between the perovskite and bismuthene promoted by the synthesis method.